A pedagogical proposal for the adaptation of the PROJETÃO Methodology to Technical courses in Informatics Integrated to High School (Research, Society and Development, 2020)
The  scenario of products and services has become increasingly competitive and varied. Information technologies have allowed a revolution in the products and services that have been offered. More and more innovative products and services have appeared. These solutions have been possible, in large part, due to advances in information technology. However, schools have not prepare students for this new scenario. Therefore, it is necessary that new innovative methodologies are also applied to the teaching-learning processes. The PROJETÃO is an innovative methodology developed by UFPE that leads students to propose innovative solutions to existing problems. PROJETÃO's innovation lies in interdisciplinarity and the focus in real-world problems. This is a qualitative exploratory study with the objective of proposing Projetec. which is a pioneering adaptation of PROJETÃO for Integrated Technical courses at Medium Level and can be applied to courses in different areas. Therefore, this adaptation makes adjustments in the development of the methodology, applied practices, group organization, insertion of new methodologies, among other actions that aim to make the methodology more suitable for integrated high school.